Faktor-Faktor yang Mempengaruhi dilakukannya Praktek-Praktek Manajemen Reproduksi Sapi Perah "Suatu penelitian yang bertujuan untuk menentukan prioritas materi penyuluhan bidang manajemen reproduksi sapi perah, kasus di Pennsylvania, USA" - Fawzia Sulaiman (Jurnal Agro Ekonomi, 1996)
The primary purpose of this research was to provide information for Perm State cooperative Extension personnels in designing extension program in the area of dairy reproductive management. The study focused on factors influencing the use of practices in five areas of reproductive management, including reproductive health, feeding management, calving and post partum management, heat detection, and artificial insemination (AI). Considering that a dairy farm profit is influenced greatly by its reproductive status, these research results could be used as a technical comparison in the efforts to increase the reproductive performance of dairy cattle in Indonesia. Research results identified several reproductive management practices which had not been used by a relatively large proportion of dairy producers. In this respect, Penn State Cooperative Extension personnels may help dairy producers to increase the reproductive efficiency of their herds by emphasizing areas where dairy producers need most help. Further, results of multiple regression analysis revealed eight factors were related significantly to the use of reproductive management practices. Those factors are: (1) dairy producers' knowledge of reproductive management, (2) DHIA (Dairy Herd Improvement Association) membership, (3) the frequency of receiving information from cooperative extension sources, (4) farmers' attitudes towards dairy farming, (5) herd size, (6) years of experience in dairying, (7) frequency of receiving information from feed company personnel, and (8) the frequency of receiving information from farm management consultant.